Soil drying shapes rhizosheath properties and their link with maize yields across different soils - Franziska A. Steiner; Shu-Yin Tung; Andreas J. Wild; Tina Köhler; Nicolas Tyborski; Andrea Carminati; Johanna Pausch; Tillmann Lüders; Sebastian Wolfrum; Carsten W. Mueller; Alix Vidal (Plant and Soil, 2025)
Background and Aims Biophysicochemical soil properties in the rhizosheath are pivotal for crop yields and drive organic carbon cycling in agricultural soils. Yet, it remains uncertain how moderate soil drought may alter and interfere with rhizosheath properties in diverse soil types, and whether specific rhizosheath traits benefit crop yields under different water availability in heterogeneous field environments. Methods Maize ( Zea mays L.) was grown under ambient precipitation and moderate drought (60% precipitation exclusion) at two field sites differing in physicochemical soil properties, such as texture and amounts of soil organic matter (SOM). Rhizosheath properties, namely soil aggregation as well as content and distribution of carbon (C) and nitrogen (N), were analyzed and, in conjunction with root traits, related to maize yields. Results Under moderate soil drought, net rhizosheath-C concentrated spatially within the smaller rhizosheath in the form of more carbon-rich rhizodeposits. These effects were mediated by native soil properties, with rhizosheath structural stability decreasing stronger under drought in the finer-textured soil, allocating greater proportions of C and N to microaggregates. Rhizosheath and root properties were associated with maize yields. Yet, the influence and importance of belowground traits for crop yields varied with environmental conditions (soil x precipitation). Conclusion The responsiveness of rhizosheath properties to moderate soil drought may influence the fate and turnover of root-derived C, and thus the overall drought resilience of SOM in agricultural soils. Moreover, our findings underscore the importance of rhizosheath properties for crop yields, yet highlighting that these relationships differ among environmental scenarios.

Riparian buffer strips promote biomass, species richness and abundance of flying insects in agricultural landscapes - Sabine Birnbeck; Johannes Burmeister; Sebastian Wolfrum; Bernd Panassiti; Roswitha Walter (Agriculture, Ecosystems & Environment, 2025)

Insects benefit from agri-environmental schemes aiming at grassland extensification - Bernd Panassiti; Sebastian Wolfrum; Sabine Birnbeck; Johannes Burmeister; Annette Freibauer; Jérôme Morinière; Roswitha Walter (Agriculture, Ecosystems & Environment, 2023)

Trichomonas gallinae infections in the naïve host Montifringilla nivalis subsp. nivalis - Sebastian Dirren; Stéphanie Borel; Nina Wolfrum; Fränzi Korner-Nievergelt (Journal of Ornithology, 2022)
Infectious diseases bear a great risk for populations of naïve host species. In the present article we inform about the first microscopic and molecular detection of the bird pathogen Trichomonas gallinae in the White-winged Snowfinch ( Montifringilla nivalis subsp. nivalis ). The emergence of trichomonosis in this highly specialised alpine bird species may pose a serious threat to its already declining population. Interspecies transmission of T. gallinae most likely occurred at a bird feeder in a Swiss mountain village. Monitoring of the disease and immediate measures to prevent its spread are urgently needed.

C4 ‐dicarboxylates and l ‐aspartate utilization by Escherichia coli K‐12 in the mouse intestine: l ‐aspartate as a major substrate for fumarate respiration and as a nitrogen source - Christopher Schubert; Maria Winter; Andrea Ebert‐Jung; Sylwia Kierszniowska; Kerstin Nagel‐Wolfrum; Thorben Schramm; Hannes Link; Sebastian Winter; Gottfried Unden (Environmental Microbiology, 2021)
Summary C4‐dicarboxylates, such as fumarate, l ‐malate and l ‐aspartate represent substrates for anaerobic growth of Escherichia coli by fumarate respiration. Here, we determined whether C4‐dicarboxylate metabolism, as well as fumarate respiration, contribute to colonization of the mammalian intestinal tract. Metabolite profiling revealed that the murine small intestine contained high and low levels of l ‐aspartate and l ‐malate respectively, whereas fumarate was nearly absent. Under laboratory conditions, addition of C4‐dicarboxylate at concentrations corresponding to the levels of the C4‐dicarboxylates in the small intestine (2.6 mmol kg −1 dry weight) induced the dcuBp‐lacZ reporter gene (67% of maximal) in a DcuS‐DcuR‐dependent manner. In addition to its role as a precursor for fumarate respiration, l ‐aspartate was able to supply all the nitrogen required for anaerobically growing E . coli . DcuS‐DcuR‐dependent genes were transcribed in the murine intestine, and mutants with defective anaerobic C4‐dicarboxylate metabolism ( dcuSR , frdA , dcuB , dcuA and aspA genes) were impaired for colonizing the murine gut. We conclude that l ‐aspartate plays an important role in providing fumarate for fumarate respiration and supplying nitrogen for E . coli in the mouse intestine.

Species–area relationships in continuous vegetation: Evidence from Palaearctic grasslands - Jürgen Dengler; Thomas J. Matthews; Manuel J. Steinbauer; Sebastian Wolfrum; Steffen Boch; Alessandro Chiarucci; Timo Conradi; Iwona Dembicz; Corrado Marcenò; Itziar García‐Mijangos; Arkadiusz Nowak; David Storch; et al. (Journal of Biogeography, 2020)
Aim Species–area relationships (SARs) are fundamental scaling laws in ecology although their shape is still disputed. At larger areas, power laws best represent SARs. Yet, it remains unclear whether SARs follow other shapes at finer spatial grains in continuous vegetation. We asked which function describes SARs best at small grains and explored how sampling methodology or the environment influence SAR shape. Location Palaearctic grasslands and other non‐forested habitats. Taxa Vascular plants, bryophytes and lichens. Methods We used the GrassPlot database, containing standardized vegetation‐plot data from vascular plants, bryophytes and lichens spanning a wide range of grassland types throughout the Palaearctic and including 2,057 nested‐plot series with at least seven grain sizes ranging from 1 cm 2 to 1,024 m 2 . Using nonlinear regression, we assessed the appropriateness of different SAR functions (power, power quadratic, power breakpoint, logarithmic, Michaelis–Menten). Based on AICc, we tested whether the ranking of functions differed among taxonomic groups, methodological settings, biomes or vegetation types. Results The power function was the most suitable function across the studied taxonomic groups. The superiority of this function increased from lichens to bryophytes to vascular plants to all three taxonomic groups together. The sampling method was highly influential as rooted presence sampling decreased the performance of the power function. By contrast, biome and vegetation type had practically no influence on the superiority of the power law. Main conclusions We conclude that SARs of sessile organisms at smaller spatial grains are best approximated by a power function. This coincides with several other comprehensive studies of SARs at different grain sizes and for different taxa, thus supporting the general appropriateness of the power function for modelling species diversity over a wide range of grain sizes. The poor performance of the Michaelis–Menten function demonstrates that richness within plant communities generally does not approach any saturation, thus calling into question the concept of minimal area.

Biodiversity assessment in LCA: a validation at field and farm scale in eight European regions - Gisela Lüscher; Thomas Nemecek; Michaela Arndorfer; Katalin Balázs; Peter Dennis; Wendy Fjellstad; Jürgen K. Friedel; Gérard Gaillard; Felix Herzog; Jean-Pierre Sarthou; Siyka Stoyanova; Sebastian Wolfrum; et al. (The International Journal of Life Cycle Assessment, 2017)

Farmland biodiversity and agricultural management on 237 farms in 13 European and two African regions - Gisela Lüscher; Youssef Ammari; Aljona Andriets; Siyka Angelova; Michaela Arndorfer; Debra Bailey; Katalin Balázs; Marion Bogers; Robert G. H. Bunce; Jean‐Philippe Choisis; Peter Dennis; Mario Díaz; et al. (Ecology, 2016)
Farmland is a major land cover type in Europe and Africa and provides habitat for numerous species. The severe decline in farmland biodiversity of the last decades has been attributed to changes in farming practices, and organic and low‐input farming are assumed to mitigate detrimental effects of agricultural intensification on biodiversity. Since the farm enterprise is the primary unit of agricultural decision making, management‐related effects at the field scale need to be assessed at the farm level. Therefore, in this study, data were collected on habitat characteristics, vascular plant, earthworm, spider, and bee communities and on the corresponding agricultural management in 237 farms in 13 European and two African regions. In 15 environmental and agricultural homogeneous regions, 6–20 farms with the same farm type (e.g., arable crops, grassland, or specific permanent crops) were selected. If available, an equal number of organic and non‐organic farms were randomly selected. Alternatively, farms were sampled along a gradient of management intensity. For all selected farms, the entire farmed area was mapped, which resulted in total in the mapping of 11 338 units attributed to 194 standardized habitat types, provided together with additional descriptors. On each farm, one site per available habitat type was randomly selected for species diversity investigations. Species were sampled on 2115 sites and identified to the species level by expert taxonomists. Species lists and abundance estimates are provided for each site and sampling date (one date for plants and earthworms, three dates for spiders and bees). In addition, farmers provided information about their management practices in face‐to‐face interviews following a standardized questionnaire. Farm management indicators for each farm are available (e.g., nitrogen input, pesticide applications, or energy input). Analyses revealed a positive effect of unproductive areas and a negative effect of intensive management on biodiversity. Communities of the four taxonomic groups strongly differed in their response to habitat characteristics, agricultural management, and regional circumstances. The data has potential for further insights into interactions of farmland biodiversity and agricultural management at site, farm, and regional scale.

Indicators for the on-farm assessment of crop cultivar and livestock breed diversity: a survey-based participatory approach - Luisa Last; Michaela Arndorfer; Katalin Balázs; Peter Dennis; Tetyana Dyman; Wendy Fjellstad; Jürgen K. Friedel; Felix Herzog; Philippe Jeanneret; Gisela Lüscher; Gerardo Moreno; Norman Kwikiriza; et al. (Biodiversity and Conservation, 2014)